Information and the Indian State: A Genealogy - Biswarup Sen (South Asia Multidisciplinary Academic Journal)
The category of information has been at the heart of notions about citizenship and governance in all modern societies. This paper constructs a genealogy of information and statehood in India by examining how information as a governing idea was brought into play in successive stages of contemporary Indian history. This first section provides a broad account of the creation of the Aadhaar card project—that attempts to uniquely identify every citizen in the country—and briefly reviews the controversies it has generated. The second portion of the paper provides historical snapshots that illustrate information’s constitutive role in previous versions of the Indian state. Thus, the second section looks at the role information played in constituting colonial government, while the next section examines the nationalist phase in pre-independence India to suggest that information functioned as speculative category that allowed freedom fighters to dream and think the nation. In the fourth section I look at the pre-liberalization period of postcolonial history to trace how information becomes a state “good” that is both strictly controlled and sparsely disseminated while at the same time acting as a spur to a specialized sort of economic activity. Finally, in the fifth and concluding section of the paper, I analyze information’s role in emerging India by revisiting the implications of the Aadhaar card in particular and of informational governance in general, by placing both in the context of contemporary political and administrative developments like the National Population Register and the Citizenship Amendment Act.